How to improve our understanding of solar wind-magnetosphere interactions on the basis of the statistical evaluation of the energy budget in the magnetosheath? - Vörös, Zoltán; Roberts, Owen W.; Yordanova, Emiliya; Sorriso-Valvo, Luca; Nakamura, Rumi; Narita, Yasuhito; Schmid, Daniel; Plaschke, Ferdinand; Kis, Árpád (Frontiers in Astronomy and Space Sciences, 2023)
Solar wind (SW) quantities, referred to as coupling parameters (CPs), are often used in statistical3 studies devoted to the analysis of SW-magnetosphere-ionosphere couplings. Here the CPs and4 their limitations in describing the magnetospheric response are shortly reviewed. We argue that a5 better understanding of SW magnetospheric interactions could be achieved through estimations6 of the energy budget in the magnetosheath (MS), which is the interface region between the7 SW and magnetosphere. The energy budget involves the energy transfer between scales,8 energy transport between locations and energy conversions between electromagnetic, kinetic9 and thermal energy channels. To reach consistency with the known multi-scale complexity10 in the MS, the energy terms have to be complemented with kinetic measures describing11 some aspects of ion- electron-scale physics.